2018
DOI: 10.4081/oncol.2018.349
|View full text |Cite
|
Sign up to set email alerts
|

Saudi anti-human cancer plants database (SACPD): A collection of plants with anti-human cancer activities

Abstract: Several anticancer drugs have been developed from natural products such as plants. Successful experiments in inhibiting the growth of human cancer cell lines using Saudi plants were published over the last three decades. Up to date, there is no Saudi anticancer plants database as a comprehensive source for the interesting data generated from these experiments. Therefore, there was a need for creating a database to collect, organize, search and retrieve such data. As a result, the current paper describes the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The anticancer activity of S. chamaecyparissus growing in Saudi Arabia was investigated by El-sharkawy (2014) , against A549, HCT116, HepG2, and MCF-7 cell lines; the study results showed that the S. chamaecyparissus was effective against HepG2 cell lines. S. chamaecyparissus also reported by other researchers as a potential plant with anticancer activity ( Elsharkawy and Aljohar, 2016 , Al-Zahrani, 2018 ). The current study findings indicated the possible role of S. chamaecyparissus in negative regulation of EGFR protein, which can be helpful in the management of human breast cancer.…”
Section: Discussionmentioning
confidence: 58%
“…The anticancer activity of S. chamaecyparissus growing in Saudi Arabia was investigated by El-sharkawy (2014) , against A549, HCT116, HepG2, and MCF-7 cell lines; the study results showed that the S. chamaecyparissus was effective against HepG2 cell lines. S. chamaecyparissus also reported by other researchers as a potential plant with anticancer activity ( Elsharkawy and Aljohar, 2016 , Al-Zahrani, 2018 ). The current study findings indicated the possible role of S. chamaecyparissus in negative regulation of EGFR protein, which can be helpful in the management of human breast cancer.…”
Section: Discussionmentioning
confidence: 58%
“…About 91 plant species from SA belonging to 38 families have exhibited anti-cancer activities against different human cancer cell lines. The plant families that have received the most attention due to their anti-cancer impact are Asteraceae (25%), Apocynaceae (10%), Fabaceae (7%), Boraginaceae (3%), and Brassicaceae (3%) [95]. For example, Catharanthus roseus L., which belongs to the Apocynaceae family, grows throughout in the Kingdom of SA, especially in the Makkah region, and it is known to contain more than 150 valuable alkaloids [96].…”
Section: Anti-cancer Activity Of Saudi Arabian Plantsmentioning
confidence: 99%
“…In the field of cancer research, plants are still a potential source for a novel chemical compound [ 2 , 3 ]. With a different biogeographic region, Saudi Arabia provides a remarkably rich source for medicinal plants that have anticancer properties [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%